BIOSYNTHESIS, CHARACTERIZATION, BACTERICIDAL AND TOXIC EFFECT OF SILVER NANOPARTICLES USING Klebsiella pneumoniae STRAIN STC1 (International Journal of Pharmaceutical Sciences and Drug Research, 2020)
Nanotechnology dealt with nanoparticles having a size of 1-100nm used significantly in pharmaceutical science and many other fields. The use of microorganisms in the synthesis of nanoparticles emerged as an eco-friendly method. Klebsiella pneumoniae strain STC1 was isolated from cow’s milk and identified by 16S rRNA sequencing. The biosynthesis was done using the fixed ratio of aqueous solution of the bacterial supernatant and AgNO3 and the colour change was observed which proved the formation of silver nanoparticles. The nanoparticles were characterized by UV-Visible Spectrophotometer, FTIR, XRD and SEM. The nanoparticles were found to have sizes ranging from 15 to 70nm. The antibacterial activity of silver nanoparticles was studied against methicillin resistant Staphylococcus aureus, Clostridium perfringens, Pseudomonas sp. and Proteus sp. The Minimum Inhibitory Concentration of silver nanoparticles was found to be 50µg/ml against methicillin resistant Staphylococcus aureus. The synergistic effect of the silver nanoparticles with commercial antibiotics erythromycin and tetracycline was found to be more evident. The time kill assay and the cytoplasm diffusion assay showed the effectiveness of synthesized silver nanoparticles in the study. The synthesized silver nanoparticles had a great antibacterial potential against methicillin resistant Staphylococcus aureus. The toxic effect of silver nanoparticles revealed that as the concentration of the silver nanoparticles increased, the effect of toxicity increased and the hatching percentage of Artemia cysts decreased. The innovation in this present study is that the biosynthesis of nanoparticles is simple, cost effective, providing good bactericidal and cytotoxic activity and it can represent a future for more therapeutic and pharmacological applications.